Relating CYP2B6 Genotype and EFV Resistance Among Women Living With HIV With High Viremia in Uganda: A Nested Cross-Sectional Study. - Buzibye, Allan; Wools-Kaloustian, Kara; Olagunju, Adeniyi; Twinomuhwezi, Ellon; Yiannoutsos, Constantin; Owen, Andrew; Neary, Megan; Matovu, Joshua; Banturaki, Grace; Castelnuovo, Barbara; Lamorde, Mohammed; Khoo, Saye; et al. (Research Square, 2021)
We investigated the association between CYP2B6 polymorphisms and efavirenz drug resistance among women living with HIV started on anti-retroviral therapy during pregnancy and with high viremia during post-partum. Methods This was a cross sectional study. Women between 6-12 weeks post-partum with viral load >1000 copies/ml were eligible. Sanger sequencing to detect resistant mutations and host genotyping were performed. We categorized efavirenz metabolizer genotype according to the AIDS clinical trials group algorithm as slow, intermediate and extensive; and compared efavirenz resistance among the metabolizer genotypes. Results Over a one-year period (July 2017-July 2018), three hundred and thirty two women were screened of whom 112 (34.8%) had viral load ≥1000 copies/ml of whom 62 had whole blood available for genotyping. Fifty-nine of these women had both viral resistance and human host genotypic results. We observed a higher frequency of efavirenz resistance among slow metabolizers (47% versus 34% in extensive and 28% in intermediate, metabolizers) but due to low numbers, this was not statistically significant. Conclusions Our findings raise the possibility that CYP2B6 polymorphism may contribute to efavirenz drug resistance in women started on antiretroviral therapy during pregnancy and with high viremia in the post-partum period. If confirmed in a larger study, this would have important implications for all patients in sub- Saharan Africa receiving efavirenz and add further support to the changes in World Health Organization policy to switch away from efavirenz as first line antiretroviral therapy in countries with a high prevalence of CYP2B6 polymorphisms.
Keywords: HIV; Pregnancy; Post-partum; CYP2B6; HIV drug resistance; Single nucleotide polymorphisms